STRATEGIC DIRECTIONS OF PUBLIC ANIMAL HEALTH MANAGEMENT IN FRANCE: EXPERIENCE FOR UKRAINE - Didok Yu. V. (Pressing Problems of Public Administration, 2021)
This paper summarizes the arguments within the scientific discussion on the issue of application of strategic management in the activities of public authorities that implement national policy in the field of animal health. The relevance of the research topic is due to the growing need of citizens to solve problems related to animal health and welfare of the territory in terms of dangerous zoonotic diseases. The main purpose of the research is to identify strategic directions of public animal health management on the example of leading European countries. The object of research is France as the country closest to Ukraine in size, administrative-territorial division, population, diversity of lands, the structure of livestock, which opens similar prospects for farmers and the food industry. The paper presents results of a study of institutional and legal bases of the system of veterinary medicine governance in France, which showed the use of strategic management. The mission of the French State Veterinary Service, which is to protect animal health, public veterinary health, the environment, have been characterized. The basic provisions of the National Animal Welfare Strategy of France for 2016–2020 have been clarified. It is noted that this Strategy is aimed at scientific support of production, strengthening veterinary controls and sanctions, innovation, modernization of the educational system, the regulation of animal abuse, empowering stakeholders at all levels. It is emphasized that the purpose of implementation of the Strategy is to mobilize the efforts of all stakeholders for the development of animal husbandry and ensure animal welfare as one of the national priorities. Public veterinary health and animal welfare have been identified as strategic directions of public animal health management in France for the last 5 years. The results of the research can be useful for drafting the mission and strategic priorities (goals) for the development of the veterinary medicine system in Ukraine, taking into account the recommendations of international organizations and the experience of developed foreign countries.